On the context‐dependent scaling of consumer feeding rates. (20th April 2016) - Barrios‐O'Neill, Daniel; Kelly, Ruth; Dick, Jaimie T. A.; Ricciardi, Anthony; MacIsaac, Hugh J.; Emmerson, Mark C.
Abstract: The stability of consumer–resource systems can depend on the form of feeding interactions (i.e. functional responses). Size‐based models predict interactions – and thus stability – based on consumer–resource size ratios. However, little is known about how interaction contexts (e.g. simple or complex habitats) might alter scaling relationships. Addressing this, we experimentally measured interactions between a large size range of aquatic predators (4–6400 mg over 1347 feeding trials) and an invasive prey that transitions among habitats: from the water column (3D interactions) to simple and complex benthic substrates (2D interactions). Simple and complex substrates mediated successive reductions in capture rates – particularly around the unimodal optimum – and promoted prey population stability in model simulations. Many real consumer–resource systems transition between 2D and 3D interactions, and along complexity gradients. Thus, Context‐Dependent Scaling (CDS) of feeding interactions could represent an unrecognised aspect of food webs, and quantifying the extent of CDS might enhance predictive ecology.